2020
DOI: 10.3389/fonc.2020.00968
|View full text |Cite
|
Sign up to set email alerts
|

Akt Inhibition Is Associated With Favorable Immune Profile Changes Within the Tumor Microenvironment of Hormone Receptor Positive, HER2 Negative Breast Cancer

Abstract: Background: The PI3K/Akt/mTOR pathway in part impacts tumorigenesis through modulation of host immune activity. To assess the effects of Akt inhibition on the tumor micro-environment (TME), we analyzed tumor tissue from patients with operable hormone receptor positive, HER2 negative breast cancer (BC) treated on a presurgical trial with the Akt inhibitor MK-2206. Methods: Quantitative multiplex immunofluorescence (qmIF) was performed using CD3, CD8, CD4, FOXP3, CD68, and pancytokeratin on biopsy and surgical s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 25 publications
1
13
0
Order By: Relevance
“…Recently, it has been found that TME plays important role in the initiation and development of cancer, especially in breast cancer 36 , 37 . Besides to cancer cell biology, the immune microenvironment (IME) that surrounding cancer cells, has also been found to affect tumorgenesis and metastasis of breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been found that TME plays important role in the initiation and development of cancer, especially in breast cancer 36 , 37 . Besides to cancer cell biology, the immune microenvironment (IME) that surrounding cancer cells, has also been found to affect tumorgenesis and metastasis of breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have also demonstrated the effect of the Akt inhibitors on TME in cancer patients. For instance, in HER2 negative breast cancer patients, two oral doses of the Akt inhibitor, MK-2206, were associated with a favorable immune profile in TME, including increased CD3 + CD8 + density and greater expression of interferon genes [ 80 ]. However, there is no study yet assessing the impact of Akt inhibition on TME in HCC patients.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…AKT can inhibit TCR/LEF/β-catenin and FOXO transcription, which are required for the function of T cell memory ( Lazarevic et al, 2013 ). Specifically, AKT inhibition can led to a favorable immune profile in the breast tumor microenvironment, including an increased density of CD3+CD8+ cells and better expression of interferon genes, providing a rationale for using AKT inhibition plus immunotherapy combination ( Marks et al, 2020 ). Correspondingly, the PI3Kβ inhibitor AZD8186 enhanced anticancer efficacy by combining with anti-PD1 Ab in PTEN-deficient xenografts ( Owusu-Brackett et al, 2020 ).…”
Section: Pi3k/akt/mtor Pathway Induces Drug Resistance In Breast Cancmentioning
confidence: 99%